What has employee loyalty to do with "love" to clients? Testing approaches to work as mediators. Issue 7 (22nd November 2022) - Kazemi, Ali; Elfstrand Corlin, Tinna
Abstract : Purpose: Drawing on the organizational psychology literature and social resource theory, this research aimed to investigate how attitude toward the employer (i.e. loyalty) and attitude toward the client (i.e. approach to work: professional, market-oriented and person-centered) relate to the perceived importance of socio-emotional resources in providing care to older people. Design/methodology/approach: Swedish frontline care staff members participated in an electronic survey using a cross-sectional design. Mediation analyses were conducted to examine proposed direct and indirect effects of loyalty on the perceived importance of socio-emotional resources in care through three different approaches to work in care settings. Findings: In general, the results confirmed the hypotheses. Thus, the analyses showed a positive association between employee loyalty and the perceived value of socio-emotional resources in care, which was partially mediated by the person-centered and professional approaches to work. Moreover, the analyses showed that the person-centered approach was more strongly related to the perceived value of socio-emotional resources in care than the other two approaches, lending support to the superiority of the person-centered approach in this context. Originality/value: The study highlights that there exist multiple approaches to work in care settings. Also, the insights about how loyalty toward the employer relates to approach to work in care settings and the perceived value of socio-emotional resources in care are novel and of crucial importance to practitioners and the outcomes of care.